Governance Components and Social Performance: Company Analysis of G20 Countries - Muhammad Farras Aroes; Fajri Adrianto; Mohamad Fany Alfarisi (Journal of Social Research, 2023)
This study is aimed to obtain empirical evidence of the influence of Management, Shareholders, and CSR Strategy on the Social Performance of companies from countries listed in the G20 forum. The study also used four control variables: Firm Size, Firm Age, Firm Leverage, and Firm Profitability. The data used is secondary data from the Thomson Reuters Eikon database of 60 companies engaged in Consumer Non-Cyclicals (Staples), more specifically, namely those engaged in the Food and Beverages sector in 2012-2021. This study used Panel Data Regression Analysis; Fixed Effect Model with the help of STATA 17. The results of this study show that Management and CSR Strategy have a significant and positive effect on Social Performance. Meanwhile, Shareholders have an insignificant and negative influence. This research adds to the high value of the scientific literature because it provides a good overview and basis for understanding how companies can provide Social Performance in accordance with company policies and performance.